O atendimento educacional especializado voltado ao estudante com a Síndrome do X-frágil - SILVA, Beatriz Sousa (2023)
This course conclusion work aimed to present two researches that discuss the actions of Specialized Educational Assistance (SEA) aimed at students who have X-Fragile Syndrome, a not-so-popular genetic condition and until then little debated among studies focused on education. Thus, the first study aimed to analyze several texts on the subject in order to describe how students who have FXS can benefit from SEA. In addition, it was necessary to bring the aspects that impede the socio-cognitive development of these students and also highlight the methodologies and strategies that SEA uses to assist in the development of students with FXS. The study presents a Scope Review with a qualitative approach, organized through the following steps: 1) identify the research question; 2) identify relevant studies; 3) select the studies; 4) map the data and 5) gather, summarize and report the results. The study, however, did not generate results, due to the absence of texts that deal with the syndrome and the SEA. Because of this, there was a need to discuss the scarcity of studies focused on Fragile X Syndrome, where information about its low prevalence, lack of data on the syndrome in Brazil and the difficulty related to diagnoses were brought. In order to complement the first research, the second study sought to bring the actions of SEA aimed at a student with Fragile X Syndrome in the city of Altamira-PA. The objectives of this study were to describe the methodologies and strategies used in SEA to contribute to the development of students with FXS, highlight the importance of family collaboration and discuss the relationship between SEA and regular education. It is, therefore, a case study with a qualitative approach, in which three teachers from the Specialized Educational Service of the same student with FXS participated in the research. The participants answered 10 structural questions sent through an online questionnaire, debts in: teacher perception about the student with Fragile X Syndrome, the role of SEA for the student with FXS and impasses faced in the search for the development of the student with the syndrome. The study revealed that despite the ludic strategies helping in the student's formation, there is no collaboration with the family and the articulation of strategies with regular education is quite fragile. However, the need to discuss the development of students with Fragile X Syndrome through the SEA, was necessary because the syndrome has characteristics that compromise the development of the individual and also because it is little known, talking about Specialized Educational Assistance was essential in order to bring into discussion the importance that this service modality can have in relation to the process of inclusion of students with disabilities, even more so in view of the many challenges that special education faces.